Malignancies of the Groin Surgical and Anatomic Considerations (Springer International Publishing, 2018)
This volume provides the first comprehensive review of the surgical anatomy of the groin in over 30 years. The text also provides a detailed review of considerations for all disciplines involved with the management of neoplasms potentially involving the inguinal lymph node basin as well as describing, in detail, the complications which can occur if one's understanding of these issues is limited. Epidemiology and the historical context in the evolution of our understanding of this anatomic area is covered along with lymphedema, one of the most concerning risks of groin surgery. Additionally, a thorough discussion of the management of all malignancies known to affect the inguinal region and quality of life is discussed. Malignancies of the Groin will be an invaluable text for any surgeon who operates on diseases of the skin, genitourinary tract, soft tissue or gynecologic tract. It will be an important adjunct for the radiation oncologist and the reconstructive surgeon and be eq ually useful for nurses, physicians assistants, nurse practitioners and other clinicians who care for patients undergoing treatment for malignancies involving the groin. The editors have compiled an international group of thought leaders in their respective disciplines to provide a broad ranging context for many of the issues that concern clinicians managing diseases affecting the inguinal region. This multidisciplinary array of authors will allow for cross-pollination of ideas from one field to another.